Dietary and lifestyle factors and its risk to kidney stone disease: a case control study at UKM Medical Centre - Nurul Nurliana Baharudin,; Suzana Shahar,; Zulkifli Md. Zainuddin, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Nutrition has been widely recognized to have certain levels of influence on the risk of kidney stone formation. Thus, this case-control study was conducted to determine the association of dietary intake and lifestyles factors with kidney stone disease. Sociodemographic data, dietary intake, supplements intake, smoking and alcohol habit, medical history, physical activity and anthropometric data were obtained using interviewer-administered pre-tested questionnaires among 81 patients who had been diagnosed with kidney stone disease and 81 patients without kidney stone disease at Universiti Kebangsaan Malaysia Medical Centre. The results indicated that body mass index and hip circumference were higher among cases as compared to controls in both men and women (p < 0.05). Energy, macronutrients and micronutrients intake were higher for case subjects compared to control subjects for all significant parameters (p < 0.05). Results showed positive association of kidney stone with consumption of nuts (≥1 time/week) for men and women while consumption of eggs (1-3 times/month) and beans (1-6 times/week) showed positive association for women. Analysis of multivariate found the risk factor among women was diabetes mellitus [Adjusted OR = 27.6 (95% CI = 1.43-53.3)] (p < 0.05). Whilst, plain water intake of at least 6 glasses [Adjusted OR = 0.001 (95% CI = 0.000-0.08)] (p < 0.05) and 8 glasses per day [Adjusted OR = 0.001 (95% CI = 0.000-0.02)] (p < 0.05) reduced the risk among women. The risk factors for men were smoking habits [Adjusted OR = 16.2 (95% CI = 1.29-203)] (p < 0.05), consumption of carbonated drink 1-3 times per month [Adjusted OR = 6.25 (95% CI = 1.04-40.7)] (p < 0.05) and 1-6 times per week [Adjusted OR = 12.5 (95% CI = 1.41-111)] (p < 0.05). Unhealthy dietary and lifestyles factors increased the risk of kidney stone disease and various risk factors were found for different sexes.